1976
DOI: 10.1677/joe.0.0710013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thyroid Status on the Thyrotrophin-Releasing Hormone-Degrading Activity of Rat Serum

Abstract: The TRH-degrading activity of rat serum in vitro is five times more potent than that of human serum. In rats, it is significantly reduced in hypothyroidism (thiouracil-induced) and significantly increased in hyperthyroidism (T3 or T4-induced). This suggests a possible role in the regulation of adenohypophysial-thyroid function which is probably, in turn, dependent on thyroid hormone, rather than TSH, levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

1978
1978
2004
2004

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 11 publications
(16 reference statements)
3
20
1
Order By: Relevance
“…In addition, we observed an increase in pyroglutamyl peptidase II mRNA in rat liver 16 h following treatment with a single dose of T 3 (table 3). It is well established that chronic T 3 treatment increases the serum level of thyroliberinase in rats [16]. In an earlier study [18] we reported no effect on serum pyroglutamyl peptidase II activity 24 h after a single subcutaneous dose of 100 µg T 3 per rat but found a significant elevation after 10 days of treatment.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In addition, we observed an increase in pyroglutamyl peptidase II mRNA in rat liver 16 h following treatment with a single dose of T 3 (table 3). It is well established that chronic T 3 treatment increases the serum level of thyroliberinase in rats [16]. In an earlier study [18] we reported no effect on serum pyroglutamyl peptidase II activity 24 h after a single subcutaneous dose of 100 µg T 3 per rat but found a significant elevation after 10 days of treatment.…”
Section: Discussionmentioning
confidence: 51%
“…Thyroid hormone was shown to increase pyroglutamyl peptidase II (thyroliberinase) activity in rat serum [16], adenohypophysis [17], frontal cortex [18] and liver [19]. The time course of the effect of thyroid hormone is consistent with a role for this hormone in increasing synthesis of pyroglutamyl peptidase II.…”
Section: Introductionmentioning
confidence: 84%
“…Another TRH antiserum with a weak titer (1:4,000) had no Thyrotropin-Releasing Hormone Antibody Blockade studies, the decrease in serum TSH persisted up to 2 h in only one experiment. Serum TRH has been reported to be similar in the normal and hypothyroid rat (39,45) and the serum TRH degrading enzyme activity lower in hypothyroid man and rat (46,47 (50) and rat pituitary cell cultures (51). Furthermore, preliminary data suggest that both serum TSH and serum Prl concentrations rise during proestrus in the rat (52).…”
Section: Discussionmentioning
confidence: 99%
“…This interpretation was supported by the findings that the activities of the particulate liver enzyme, like the serum enzyme [16][17][18], is also regulated by thyroid hormones [19]. Moreover, similar enzymechemical properties between the particulate liver enzyme and the serum enzyme were noticed [9,15].…”
mentioning
confidence: 62%